LITERASI MATEMATIS SISWA PADA KONTEN CHANGE AND RELATIONSHIP DITINJAU DARI GAYA BELAJAR SISWA - Nariyati, Rini Yurika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to describe the level mathematical literacy which can be achieved by the students on Change and Relationship content to the eighth-grade students of SMPN 07 Kubu Raya observed from their learning style. Method used was descriptive in form survey. The subject in this research was 22 students of the VIII B class of SMPN 07 Kubu Raya. Tools of data collection are written test to discover the level of studentsâ€™ mathematical literacy on Change and Relationship content; questionnaire to cluster based on their learning style; and interview as the follow up. The data analysis results showed that the studentsâ€™ mathematical literacy on Change and Relationship content with auditory learning style achieved varied mathematical literacy, such as the level of 1,3,5, and 6, the students with visual learning style achieved varied mathematical literacy such as the level of 1,2,3,5, and 6, and the students with kinesthetic learning style achieved varied mathematical literacy such as the level of 1,4, and 5.Keywords: Mathematical Literacy, Change and Relationship Content, Learning Style, Algebra Expression. Â